Faktor yang Memengaruhi Auditor Switching di Indonesia - Retna Safriliana; Siti Muawanah (Jurnal Akuntansi Aktual, 2019)
Abstract: The purposes of this research are to examine the effect of audit opinion, public accounting firm size, financial distress and audit committee on auditor switching. This research is qualified as a confirmation research. Auditor switching is a change of public accountant firms at a certain time as stipulated by Regulation of the Ministry of Finance No.17/PMK.01/2008 concerning Public Accounting Services which has been revised to No.KEP-86/BL/2011, that the provision of Public Audit services for six consecutive years by Public Accounting Firm and three consecutive years by a public accountant with one client. The research sample is selected with random sampling method and includes 300 data, taken from 50 manufacturing companies listed in Indonesia Stock Exchange in 2011-2016. Logistic regression is used for analysing the data, and auditor switching is measured by dummy variables. The results of this study show that public accounting firm size and audit committee affect the auditor switching, while the audit opinion and financial distress does not affect the auditor switching.Abstrak: Tujuan dari penelitian ini adalah untuk menguji dampak dari opini audit, ukuran kantor akuntan publik, financial distress dan komite audit pada auditor switching. Penelitian ini tergolong dalam penelitian konfirmatori. Auditor switching adalah pergantian dari Kantor Akuntan Publik pada waktu tertentu sebagaimana ditetapkan oleh Surat Keputusan Menteri Keuangan No.17/PMK.01/2008 tentang Jasa Akuntan Publik yang telah direvisi menjadi No.KEP-86/BL/2011, yang memberikan jasa Audit Publik selama enam tahun berturut-turut oleh KAP dan tiga tahun berturut-turut oleh satu akuntan publik dengan klien yang sama. Sampel penelitian dipilih dengan cara acak dan berjumlah 300 data, yang diambil dari 50 perusahaan manufaktur di Bursa Efek Indonesia di tahun 2011-2016. Alat analisis data yang digunakan adalah Regresi Logit, dan auditor switching diukur dengan menggunakan variabel dummy. Hasil dari studi ini menunjukkan bahwa ukuran KAP dan komite audit mempengaruhi auditor switching, disamping itu opini audit dan financial distress tidak mempengaruhi auditor switching.